The Influence of Educative Puzzle Game to Concentration of Children with Attention Deficit and Hyperactivity Disorder In Arogya Mitra Acupuncture Klaten. (July 2019) - Suyami,; Khayati, FN; Setianingsih,; Pranandari, C
Abstract: ADHD is characterized by attention deficit, impulsivity and hyperactivity disorder that is not in accordance with the child's developmental stage. These conditions certainly can cause various problems such as learning, behavior, and social difficulties, and one of them is difficult to concentrate. One of the efforts to increase concentration on children with ADHD is through educative puzzle game. This study aimed to determine the effect of educative puzzle game on concentration of children with ADHD. The study design used was pre-experimental with the one group pretest and posttest design. We used purposive sampling to collect the sample with total samples were 15 respondents. We used concentration questionnaire as an instrument and we analyzed with paired t-test. Concentration scores before given the educative puzzle game was 7.53 (SD ±3.021), which was in the low category. Meanwhile, concentration scores after given the educative puzzle game was 11.80 (SD ±4.074) win the medium category. The score increased about 4.27. Paired t-test results showed p value < alpha (0, 000 <0.05). The conclusion of this study suggests that educative puzzle game affect the concentration of children with attention deficit and hyperactivity disorder (ADHD) in Arogya Mitra Acupuncture Klaten.